Influence of post-mortem aging time and method on flavor and tenderness of beef, and comparison of retail cutting yields, times, and value in thirteen beef subprimals from beef and Holstein cattle - Foraker, Blake Austin, author; Woerner, Dale R., advisor; Belk, Keith E., committee member; Engle, Terry E., committee member; Heuberger, Adam L., committee member (Colorado State University. Libraries, 2018)
The objective of this study was to identify flavor and tenderness differences in beef aged for different lengths of time and using different methods. Strip loin sections from commodity, USDA Choice beef carcasses (n = 38) were randomly assigned to 1 of 8 aging treatments: 1) 3 d wet-aged; 2) 14 d wet-aged; 3) 28 d wet-aged; 4) 35 d wet-aged; 5) 49 d wet-aged; 6) 63 d wet-aged, 7) 21 d dry-aged; and 8) 14 d wet-aged followed by 21 d dry-aged (combination). Trained sensory panelists rated the cooked product for flavor and textural attributes, and samples were evaluated for Warner-Bratzler and slice shear force, fatty acid composition, amino acid composition, and volatile flavor compounds. Wet-aging of beef up to 35 d caused no changes (P > 0.05) in flavor notes. However, beef wet-aged for 49 d or longer was rated lowest (P < 0.01) for the attribute of beef flavor ID and greatest (P ≤ 0.02) for metallic, sour, oxidized, nutty, musty/earthy, and liver-like. No differences (P > 0.05) were identified between wet-aging, dry-aging, or the combination of both for any flavor attributes. Fatty acid profiles did not differ (P > 0.05) by aging length of time or method. Concentrations of amino acids and volatile flavor compounds increased (P < 0.01) during the wet-aging period, but minimal differences in these compounds were noted between wet- and dry-aged beef. Additionally, beef that was wet-aged for 3 d was toughest (P < 0.01). Nonetheless, tenderness improvement only occurred up to 28 d of wet-aging, where no subsequent differences (P > 0.05) were noted. Results suggested that wet-aging to extreme lengths of time may have a dramatic effect on flavor profile of beef, without necessarily improving tenderness. Additionally, eating quality characteristics do not necessarily differ between wet- and dry-aged beef. Holsteins comprise approximately 20% of the U.S. fed beef slaughter, and the carcass characteristics of Holsteins tend to differ (on average) from those of traditional beef breeds. Retail cutting yields, cutting times, and resulting value were evaluated in thirteen subprimal cuts from carcasses of fed Holstein (n = 398) and beef-breed (n = 404) origin. Generally, subprimals from carcasses of beef-breeds were heavier (P < 0.05) than those derived from Holsteins. Greater (P < 0.01) saleable yields of retail cuts were noted for ribeye rolls, short loins, and inside rounds (individual muscle) from carcasses of Holsteins, and bottom round flats from carcasses of beef-breeds. Saleable yields of all other subprimal cuts did not differ (P > 0.05) between cattle types. Only the amount of time taken to cut center-cut top sirloin butts derived from beef-breeds were faster (P < 0.01) than those for cuts from carcasses of Holsteins; in all other instances, times for cutting subprimals derived from Holstein carcasses were either faster (P < 0.05) or not different (P ≥ 0.05). Retail prices among cuts from differing breed types were minimal, but true differences (P < 0.05) in cutting yields for ribeye rolls and short loins from carcasses of Holsteins may generate greater values to a steak cutter or retailer. Such advantages could be attributed to smaller, more manageable, and leaner cuts produced from carcasses of Holsteins. Therefore, further research regarding retail cutting differences between cattle types may provide insight for operations seeking maximum retail yields and profit.